Factors Causing Low Regeneration of Rice Farmers in Mandastana District, Barito Kuala Regency - Fitria Fitria; Deasy Arisanty; Nevy Farista Aristin; Karunia Puji Hastuti; Parida Angriani (The Innovation of Social Studies Journal, 2025)
Farmer regeneration is one of the problems in the agricultural sector, this is because most farmers are classified as old and few young people are interested in continuing to work in the agricultural sector. This study aims to analyze the factors causing the low regeneration of rice farmers. The study was conducted in Mandastana District, Barito Kuala Regency, Indonesia. The subjects of this study were children of farmer group members in Mandastana District with an age range of 16-35 years. The sample taken was 365 people using the proportionated random sampling technique. This study uses a descriptive quantitative research method. Data collection used in this study was observation, questionnaires (semi-closed) and documentation. The analysis used in this study was factor analysis or Principal Component Analysis (PCA). The results of the study showed that the first factor or the most dominant factor causing the low regeneration of farmers was the level of education, information from outside and peers, with correlation values of 0.931, 0.796 and 0.705. The second factor that causes low regeneration of rice farmers is the area of land ownership, work experience in the agricultural sector, family income from the agricultural sector, family income from the agricultural sector and family socialization, with correlation values of 0.689, 0.730, 0.859 and 0.833. The third factor that causes low regeneration of rice farmers is wages outside the agricultural sector, with a correlation value of 0.934.